Current Views on Clinical Oncology Training from the 2015 Oncology Registrars' Forum Survey. Issue 9 (September 2016) - Kosmin, M.; Brown, S.; Hague, C.; Said, J.; Wells, L.; Wilson, C.
Abstract: The major role of the Oncology Registrars' Forum (ORF) of the Royal College of Radiologists is to voice the opinions of the clinical oncology trainee body and work towards improving all aspects of clinical oncology training in the UK. In order to provide data to support these efforts, the ORF undertakes a biennial survey of all trainees. As with the previous surveys, this year's ORF survey produced data that highlight areas of good training as well as new and ongoing areas of concern. This summary highlights the key survey results and provides recommendations for improving the delivery of clinical oncology training in the UK. Highlights: Trainees' views on all aspects of UK clinical oncology training are summarised. Concerns include unfilled training posts and involvement in general medical rotas. Recommendations are made for improvements to clinical oncology training.